Present status of maize diseases in the humid forest and western highlands of Cameroon - Ngoko, Z.; Cardwell, K.F.; Marasas, W.F.O.; Tchamo, P; Tagne, A.; Mwangi, M; Wingfield, M.J. (2007)
Maize disease surveys were conducted between 1995 and 2004 inthe Republic of Cameroon. A total of 260 farms in 36 villages, ranging from low altitudes with bimodal rainfall distribution to high altitudes with monomodal rainfall, were included in the surveys. ln the humidforest, Bipolaris maydis and Puccinio polysora were the prevalent fungi with a mean incidence of 70% in 1995 and 44% in 2004. Rhizoctonia solani, Stenocarpella mocrospora, and Physodermo maydisoccurred at low incidence levels in all the villages. In the western highlands, Exserohilum turcicum and Cercospora zeae-maydis were the prevalent pathogens, with incidence ranging from 16% to 100% in 1995-1998. In 2004, the mean incidence for the pathogens ranged from 30 to 95%. Phaeosphaeria maydis, the most severe pathogen (incidence=70%) in 1995, has been displaced by Cercospora zeae-maydis (incidence=60%). The incidences of sporisorium reilianum and Puccinia sorghi were about 5% in 1998; in 2004, the incidence of S.reilianum had increase d to 20%. In many of the farms surveyed, most of these diseases occurred in association. There was a positive correlation between incidence of Puccinia polysora and that of Bipolaris maydis in the humid forest. Phaeosphaeria leaf spot vvas negatively correlated with C. zeae-maydis and E. turcicum in the western highlands. Although some diseases were prevalent in specific ecological niches, E. turcicum was found in both highlands and lowlands but with low incidence in the latter areas. Fusarium, Aspergillus species and Diplodia maydis were the most important mycotoxin-producing fungi that caused ear rots in the western highlands in 2004.